THE EFFECT OF DIVERSITY, ORGANIZATIONAL CLIMATE, AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON VOCATIONAL SCHOOL TEACHERS IN SOUTH JAKARTA - Karyaningsih, RR Ponco Dewi; Rachmadania, Rizki Firdausi; Yusran, Ilyas Pratama (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
The purpose of this study was to determine the effect of Diversity, Organizational Climate and Organizational Commitment on Organizational Citizenship Behavior in State Vocational High School Teachers in South Jakarta. The research method used is a survey method using a descriptive approach with the population used are State Vocational School teachers in South Jakarta. This research model uses path analysis model. The analytical technique used is SEM (Structural Equation Modeling) which is operated with SmartPLS 3.0 software for hypothesis testing. The analysis technique carried out in PLS includes three stages, namely external model analysis, internal model analysis, and hypothesis testing. The results obtained from this study include a positive and significant influence on the diversity of organizational citizenship behavior, climate on organizational citizenship behavior, diversity on organizational citizenship behavior and diversity, organizational climate,and organizational commitment to organizational citizenship behavior.